Community Based Assessment of Biochemical Risk Factors for Cardiovascular Diseases in Rural and Tribal Area of Himalayan Region, India - Ashok Kumar Bhardwaj; Dinesh Kumar; Sunil Kumar Raina; Pradeep Bansal; Satya Bhushan; Vishav Chander (Biochemistry Research International)
Context. Evident change in nutrition and lifestyle among individuals of urban and rural areas raises suspicion for similar change in tribal area population of India. Aim. To study the biochemical risk factor for CVDs in rural and tribal population of Sub-Himalayan state of India. Settings and Design. Cross-sectional study in rural (low altitude) and tribal (high altitude) area of Himachal Pradesh, India. Methodology. Blood lipid profile using standard laboratory methods. Statistical Analysis. Chi-square test and multiple linear regression analysis. Results. Total of 900 individuals were studied in both areas. As per Asian criteria, obesity (BMI 27.5–30.0 kg/m2) was observed to be significantly high (P=0.00) as 13.7% in tribal area as compared to 5.5% in rural area. Normal level of TC (<200 mg/dL) and LDL (<130 mg/dL) was observed in the majority of the population of both areas, whereas, at risk level of HDL (<40 mg/dL) was present in half of the population of both rural and tribal areas. The prevalence of borderline to high level of TGs was observed to be 60.2% and 55.2% in rural and tribal (P=0.10) area, respectively. Conclusion. Prevalent abnormal lipid profile in tribal area demands establishment of an effective surveillance system for development of chronic diseases.